PENGALAMAN MAHASISWA MENJALIN PEER RELATIONSHIP DI LINGKUP KAMPUS - Daud Alfizar Parulian Manalu; Muhammad A. Ferdiansyah; Amanda P. Septriani; Alrefi (Journal of Counseling Support, 2025)
Abstract Students are in a transitional period towards adulthood that requires them to develop academically, socially, and emotionally. One important aspect of students social development is their ability to form peer relationships. Ideally, friendships between students should be positive. However, in reality, there are still conflicts between friends, unhealthy competition, lack of empathy, and individualistic attitudes. This condition prompted researchers to find the reasons behind this gap. This study aims to gain an in-depth understanding of students' experiences in forming peer relationships on campus. The approach used is qualitative with a phenomenological method. The research subjects consisted of three Sriwijaya University students from three different faculties selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using the Miles and Huberman model. The results of the study show that students experiences in establishing peer relationships on campus vary greatly. First, cooperation among students is built through good communication, a sense of responsibility, and fairness. Second, competition among students can be a source of motivation as well as conflict. Third, students have various ways of resolving problems in their friendships. These findings indicate that peer relationships among students are a dynamic process influenced by individual factors and the social situation on campus.